Non-invasive computer navigation can quantify the pivot shift maneuver with good to excellent reliability in healthy volunteers - Edoardo Monaco; Giorgio Bruni; Sara Lo Torto; Alessandro Carrozzo; Matthew Daggett; Alessandro Annibaldi; Adnan Saithna; Andrea Ferretti (Journal of Experimental Orthopaedics, 2020)
Abstract Purpose The aim of this study was to determine the inter- and intra-observer reliability of knee laxity assessment using a non-invasive navigation system in a population of healthy young athletes. It was hypothesized that knee laxity parameters recorded using non-invasive computer navigation would demonstrate good inter- and intra-observer reliability. Methods Healthy volunteers aged between 18 to 30 years were recruited to the study. Static and dynamic knee laxity parameters including anterior tibial translation and tibial rotation during the pivot shift test were recorded on awake patients using non-invasive computer navigation by two independent observers: at the first visit each athlete was evaluated by the consultant and resident surgeons independently; 6 weeks after the first visit all the participants were re-tested only by the resident surgeon. Inter- and intra-observer reliability was calculated and then interpreted according to Cicchetti’s criteria. Results One hundred healthy volunteers were recruited to the study, of these 38 were women (38%), and the average age was 25.5 ± 2.4 years. According to Cicchetti’s criteria the intra- and inter-observer reliability for static measurements were fair for anterior tibial translation (0.572 and 0.529, respectively) and excellent for total passive tibial rotation (0.859 and 0.883, respectively). For the dynamic measurements of translation and rotation during the pivot shift maneuver both measurements demonstrated good to excellent reliability with intra and inter observer reliability ranging from 0.684 to 0.936. Conclusion Non-invasive navigation for the assessment of knee laxity is associated with fair to excellent inter- and intra-observer reliability in a population of healthy volunteers.